2022
DOI: 10.3389/fneur.2022.1027104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dual-task training in patients with post-stroke cognitive impairment: A randomized controlled trial

Abstract: BackgroundEvidence for the efficacy of cognitive-motor dual-task (CMDT) training in patients with post-stroke cognitive impairment (PSCI) and no dementia is still lacking. More importantly, although some studies on the cognitive effect of CMDT training show an improvement in cognitive performance, the results are still controversial, and the intervention mechanism of CMDT training on cognitive function improvement is not clear. The main purpose of this study was to analyze the effects of CMDT training on cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Ultimately, 47 studies met the inclusion criteria. Additional searches in the references of published systematic reviews identified three more eligible studies, resulting in 50 randomized controlled trials included ( Chen et al, 2006 , 2019 , 2020 ; Liu et al, 2006 , 2019 , 2022 ; Ou et al, 2007 ; Shin et al, 2008 ; Yang and Liu, 2008 ; Wang et al, 2009 , 2013 ; Li and Gan, 2010 ; Kim et al, 2011 ; Zhang et al, 2012 , 2018 , 2020 ; Feng et al, 2014 ; Ye et al, 2014 ; Zucchella et al, 2014 ; Xu et al, 2015 ; Yoo et al, 2015 ; Li M. et al, 2016 ; Li X. et al, 2016 ; Cao et al, 2017 ; Gong, 2017 ; Jiang et al, 2017 ; Li et al, 2017 ; Lv et al, 2017 ; Maier et al, 2017 ; De Luca et al, 2018 ; Prokopenko et al, 2018 , 2019 ; Xiao, 2018 ; Mao et al, 2019 ; Wang, 2019 ; Xiao and Liang, 2019 ; Yeh et al, 2019 , 2022 ; Faria et al, 2020 ; Fu et al, 2020 ; Jung et al, 2020 ; Shao, 2021 ; Xuefang et al, 2021 ; Ho et al, 2022 ; Liao et al, 2022 ; Shang et al, 2022 ; Sun et al, 2022 ; Xia et al, 2022 ; Zhao et al, 2020 , 2022 ). The specific screening process is depicted in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ultimately, 47 studies met the inclusion criteria. Additional searches in the references of published systematic reviews identified three more eligible studies, resulting in 50 randomized controlled trials included ( Chen et al, 2006 , 2019 , 2020 ; Liu et al, 2006 , 2019 , 2022 ; Ou et al, 2007 ; Shin et al, 2008 ; Yang and Liu, 2008 ; Wang et al, 2009 , 2013 ; Li and Gan, 2010 ; Kim et al, 2011 ; Zhang et al, 2012 , 2018 , 2020 ; Feng et al, 2014 ; Ye et al, 2014 ; Zucchella et al, 2014 ; Xu et al, 2015 ; Yoo et al, 2015 ; Li M. et al, 2016 ; Li X. et al, 2016 ; Cao et al, 2017 ; Gong, 2017 ; Jiang et al, 2017 ; Li et al, 2017 ; Lv et al, 2017 ; Maier et al, 2017 ; De Luca et al, 2018 ; Prokopenko et al, 2018 , 2019 ; Xiao, 2018 ; Mao et al, 2019 ; Wang, 2019 ; Xiao and Liang, 2019 ; Yeh et al, 2019 , 2022 ; Faria et al, 2020 ; Fu et al, 2020 ; Jung et al, 2020 ; Shao, 2021 ; Xuefang et al, 2021 ; Ho et al, 2022 ; Liao et al, 2022 ; Shang et al, 2022 ; Sun et al, 2022 ; Xia et al, 2022 ; Zhao et al, 2020 , 2022 ). The specific screening process is depicted in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…While most studies detailed their randomization process, 13 did not specify the method of random sequence generation. Only one study ( Sun et al, 2022 ), described allocation concealment, leading to the classification of the others as having an ‘unknown risk’ of bias in this regard. Due to the nature of the interventions, blinding of participants was not feasible.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations